Anti-oxidant activity research of enzymatic biomarkers in protozoa (Paramecium sp.) under stress by manufactured nanoparticles - KHALDI, F; GRARA, N (My University, 2017)
The production of nanoparticles (NPs) is increasing rapidly for electronics, chemistry and biology applications. This interest is due to the very small size of NPs which provides them with many interesting properties such as rapid diffusion, high specific surface areas, reactivity in liquid or gas phase and a size close to bio-macromolecules. However, these extreme abilities might be a problem when considering a potentially uncontrolled exposure to the environment. For instance, nanoparticles might be highly mobile and rapidly transported in the environment or inside the body through a water or air pathway. Accordingly, the very fast development of these new synthetic nanomaterials raises questions about their impact on the environment and human health. We have studied the impact of manufactured nanoparticles (ZnO) on ciliated microorganisms (Paramecium sp.).Principles results show that the ZnO presence affects the paramecia growth. On the metabolic level, ZnO causes a disturbance in the rate of total protein and total carbohydrates. Regarding the biomarkers we identified disruption of glutathione (GSH)and catalase (CAT)activity. This study shows the importance of a model species for assessing the ZnO toxicity in laboratory tests. It is clear that ZnO is the oxidative stress source, which results in a stimulation of growth in Paramecium sp.,a disturbance in the total protein rate, carbohydrates, glutathione and catalase activity